2022
DOI: 10.1002/hyp.14763
|View full text |Cite
|
Sign up to set email alerts
|

Impact of soil texture and salt type on salt precipitation and evaporation under different hydraulic conditions

Abstract: Salt precipitation and evaporation in porous media is an important research topic. However, several aspects remain controversial; notably, whether efflorescence inhibits evaporation in wet soil, the influence of soil texture on salt crust formation and the effect of sulphate precipitation on evaporation under changing hydraulic conditions. Therefore, this study investigates the influence of salt type (NaCl and Na2SO4) and soil texture (sandy soil, sandy loam and silt loam) on salt precipitation and evaporation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…Salt crystallization continued to grow slowly until the end of the experiment (15 days), when efflorescence completely covered the soil surface in treatment S1, while efflorescence in treatment S2 covered only 70% of the soil surface area. This result is similar to that reported by Li et al (2022), where the efflorescence of NaCl treatments exhibited a higher coverage rate and covered a larger area compared to Na 2 SO 4 treatments.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Salt crystallization continued to grow slowly until the end of the experiment (15 days), when efflorescence completely covered the soil surface in treatment S1, while efflorescence in treatment S2 covered only 70% of the soil surface area. This result is similar to that reported by Li et al (2022), where the efflorescence of NaCl treatments exhibited a higher coverage rate and covered a larger area compared to Na 2 SO 4 treatments.…”
Section: Resultssupporting
confidence: 92%
“…Soil evaporation processes are usually affected by aerodynamic resistance and soil dry layer resistance. Moreover, previous studies reported that evaporation in saline soils is also affected by the resistance arising from salt crystallization (Fujimaki et al, 2006; Li et al, 2022; Li & Shi, 2019; Zhang et al, 2014). In this study, the effect of wind speed on evaporation was not considered; therefore, for the evaporation process, dry layer resistance and salt crystallization resistance were primarily considered, and they were calculated as follows: E=CitalicvsCitalicvaRs+Ritalicsc$$ E=\frac{C_{vs}-{C}_{va}}{R_s+{R}_{sc}} $$ where C v is the water vapour concentration (kg m −3 ) and subscripts s and a denote soil and air, respectively, R s is the soil dry layer resistance (m s −1 ), and R sc is the salt crystallization resistance (m s −1 ). Cv=es×Mw×HrRT+273.15$$ {C}_v=\frac{e_s\times {M}_w\times {H}_r}{R\left(T+273.15\right)} $$ es=611×exp17.502×TT+240.97$$ {e}_s=611\times \exp \left(\frac{17.502\times T}{T+240.97}\right) $$ where e s is the saturated water vapour pressure (Pa), M w is the molar mass of water (kg mol −1 ), H r is the relative humidity (%), R is the universal gas constant (J mol −1 K −1 ), and T is the soil surface temperature or air temperature (°C).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations